Constructions of masculinity in the Middle East and North Africa : literature, film, and national discourse - Kahf, Mohja, 1967-; Sinno, Nadine (The American University in Cairo Press, 2021)
Constructions of masculinity are constantly evolving and being resisted in the Middle East and North Africa. This book examines constructions of both hegemonic and marginalized masculinities in the MENA region, through literary criticism, film studies, discourse analysis, anthropological accounts, and studies of military culture. This book spans the colonial and postcolonial eras with emphasis on the late twentieth century to the present day.